Law professors’ existential online lifeworlds: an hermeneutic phenomenological study - Myers, Cheryl (Kansas State University, 2017)
This phenomenological study hermeneutically explores law professors’ felt experiences within online existential lifeworld spheres. Prose, poetry, color images, and virtual journeying provide descriptive and interpretive text suggesting expansion of Gadamer’s fusion of horizonal understanding. Law professors who teach asynchronously online selected five color images from pixabay.com corresponding with the five universal existential themes: body, space, time, relationships and material things/technology (van Manen, 2014) as catalysts to conversationally explore what it feels like to transition from classroom to online instruction. Multiple phenomenological, artistic, and scientific theories prismatically amplify and explain the study’s design: Gadamer’s hermeneutical circle of understanding (1960/2006), Termes six-point spherical perspective (2016), Einstein’s closed yet unbounded universe (Egdall, 2014), and Seamon’s concept of “at homeness” (2012). Dialogical understanding of Self and Other(s) through Gadamer’s call for festival and serious play (1960/2006) is activated: The reader is invited to interact with the study text through visual and auditory web experiences. Researcher’s hermeneutic and existential retelling of the professors’ conversations begins to unfold metaphorically around a table within a virtual forest. When researcher’s previously bracketed-away prejudice for incorporating synchronous modalities into online learning erupts, professors’ longing felt for classroom home actualizes and ultimately emerges as a sixth existential dimension proposed by the researcher. A culminating journey through virtual desert in search of online home continues the retelling and metaphorically incorporates all six existential themes. Dramatic changes in researcher’s lifeworld view, ways of knowing and being, self view, self action and pedagogical development as a result of conducting the study are summarized. Future research is implicated including exploration of professors’ existentially felt experiences while teaching synchronously online and deep-mining professorial empathy toward students. Factors that impinge on all law professors’ transitioning to online instruction contextually anchor the study: 1) Legal pedagogy’s evolution from 18th Century professional skills training through the late 19th Century intrusion of legal doctrine instruction, and 20th Century paralegal skills training; 2) The American Bar Association’s 21st century mandates for graduating students with both legal skills and legal doctrine training; 3) 21st Century pedagogical Immutables (teaching online, teaching legal job skills, teaching legal doctrine, teaching to standardized tests); and 4) 21st Century Protean Challenges (institution and student demand for technology-based instruction, the Global Legal Services Industry’s hierarchical control over legal education and practice, enrollment and tuition crises, multi-cultural limitations, and the pedagogical conundrum of choosing among multiple online design and delivery modalities).
Keywords: E-learning; Existential lifeworlds; Law professors; Arts-based research; Color imagesHermeneutic phenomenological research